Molecular characterization and phylogenetic analysis of dengue viruses imported into Taiwan during 2011-2016 - Yang, Cheng-Fen; Chang, Shu-Fen; Hsu, Tung-Chien; Su, Chien-Ling; Wang, Tzy-Chen; Lin, Shih-Hung; Yang, Su-Lin; Lin, Chien-Chou; Shu, Pei-Yun (PLoS neglected tropical diseases, 2018)
A total of 1,596 laboratory-confirmed imported dengue cases were identified in Taiwan during 2011-2016. Most of the imported cases arrived from Southeast Asia as well as the Indian subcontinent, the Pacific region, Latin America, Australia and Africa. Phylogenetic analyses of the complete envelope protein gene sequences from 784 imported dengue virus (DENV) isolates were conducted, and the results suggest that the DENV-1 genotype I and DENV-2 Cosmopolitan genotype comprise the predominant serotype/genotype of DENV strains circulating in Southeast Asia. The DENV-1 genotype III, DENV-3 genotype III and DENV-4 genotype I and II strains were found to be newly emerging in several Southeast Asian countries. Our results also showed that geographical restrictions of DENV-1 genotype I, DENV-1 genotype III and DENV-2 Cosmopolitan genotype are becoming blurred, indicating the extensive introductions and continuous expansions of DENV strains between nations in Southeast Asia. In this study, we present the geographic distribution and dynamic transmission of DENV strains circulating in Southeast Asian countries. In addition, we demonstrated local dengue epidemics caused by several imported DENV strains in Taiwan during 2011-2016.